Pediatric hypertensive emergency: a rare case report of metanephrines negative pheochromocytoma - Goel, Neha; Khatri, Hardeep; Kumar, Sandeep; Gupta, Ratan (International Journal of Contemporary Pediatrics, 2025)
Pheochromocytomas are catecholamine-secreting paragangliomas (PPGL) arising from chromaffin cells in the body. It is a rare cause of secondary hypertension in adults but is even rarer in children. Ten percent occur in children, in whom they present most frequently in the age group 6-14 years. The annual incidence among children is approximately 0.8/1000000 person-years. A 7-years-old child presented with hypertensive emergency and differences in blood pressure between the upper and lower limbs > 10 mmHg. Contrast-enhanced computed tomography of the abdomen suggested the diagnosis of right-sided pheochromocytoma. Urine and plasma metanephrines were within normal limits. The hypertensive emergency was managed with anti- hypertensives and the mass was surgically resected which was confirmed as malignant Pheochromocytoma on histopathology. Pheochromocytoma can be diagnosed by measurement of 24-hour urinary or plasma metanephrines which has sensitivity and specificity of nearly 95% and 85%. However, in our case these levels were normal. It could be because of rarest dopamine-producing PPGL which produces more dopamine than the combined concentration of epinephrine and nor-epinephrine. Dopamine secreting PPGL are rare entities. This case has changed our approach to the long-term follow-up and observation of this patient, which consists of more regular clinical review and imaging with positron emission tomography – computed tomography (PET/CT) as opposed to follow up of a benign tumor and earlier discharge into the community.